Sistem Informasi Kinerja Pegawai Non-ASN Berbasis Web pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Situbondo - khoiron, alva alvin; Adi Susanto; Ayung Warninda (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
The Population and Civil Registration Office of Situbondo Regency faces challenges in improving the efficiency of recording and reporting the performance of Non-ASN employees, which has so far been conducted through temporary notes and documents. This approach is prone to delays, input errors, and suboptimal data management. To address this issue, this study aims to design a web-based information system capable of recording, managing, and displaying Non-ASN employee performance reports in a structured and real-time manner. The system is developed using PHP programming language and MySQL database to support dynamic and integrated data management. The system development follows the V-Model approach, which emphasizes verification and validation at each development stage, including requirement analysis, system design, module design, implementation, unit and integration testing, and maintenance. The result of this study is an information system that facilitates performance data entry, accelerates report generation, and improves accuracy and transparency in evaluating Non-ASN employee performance. In addition, the system is designed with a responsive web interface that is easy for stakeholders to use.